Penggunaan teknik reaksi rantai polimerase (PCR) DNA proviral dari virus enzootic bovine leukosis - Retno D. Soejoedono (Hemera Zoa, 1991)
A polymerase chain reaction was developed to detect the proviral DNA of bovine leukimia virus in bovine lymphocytes. Milk and blood samples from infected and uninfected cows were tested. None of the bovine leukosis free animals gave a positive response and 58% of the infected cows showed positive signals. When the DNAs 25ul of blood. 25.000 lymphocytes or 1.000 lymphocytes were amplified. positive results were recorded more frequently in cows with persistent  lymphocytes than in cows with normal  lymphocyte counts.